Determination of ethanol in low-alcohol fermented beverages - Bortoleto, Gisele Gonçalves; Gomes, Winston Pinheiro Claro (Revista Sítio Novo, 2022)
Due to the exaggerated worldwide consumption of alcoholic beverages the development of special fermented beverages with low alcohol content or without alcohol is an interesting market niche. Thus, this study aims to quantify the ethanol content of commercial fermented beverages labelled “low alcohol content” or “without alcohol” and evaluate it in order to guarantee the safety of the beverage for its consumers. For this, the ethanol quantification was performed in eleven samples by gas chromatography with headspace and flame ionization detection (HS-GC-FID) and the method has to be successful. Four samples were in agreement with the legislation, six presented ethanol above recommendations and one of them presented ethanol content below the value labelled. These results show that it is necessary an improvement on analytical controls by industries and also a more active inspection of regulatory organizations to guarantee the consumers safety.